Neonatal Diagnosis and Treatment of Menkes Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Infants diagnosed with Menkes disease early by plasma neurochemical methods and treated early, within 22 days after birth, with copper replacement therapy, had a 92% survival rate vs 13% in those treated late, Median follow-up in 12 newborns treated early was 4.6 years compared to 1.8 years in 15 diagnosed and treated late.